Environmental Quality and Health Status in SAARC Countries: Assessing the Impact of Pollution, Economic Growthand Public Services on Life Expectancy (Journal of Asian Development Studies, 2025)
The study evaluates the nexus between environmental quality and health status in sevenSAARC countries by using life expectancy as a proxy for health status. Thenexus is being investigated by using the panel data from 2000 to 2023. CS-ARDL approach is used to find out both the short-run and long-run results. Life expectancy is employed as dependent variable while the key independent variables are CO2 emissions, PM2.5 and ecological footprint. These three variables represent our main variable that is environmental quality. Moreover, GDP growth, urban population, sanitation services, prevalence of undernourishment, unemployment and health expenditures also used in the paper as independent variables. The findings indicates that GDP growth, urbanization, health expenditures and sanitary services has a positive impact on life expectancy. While, the life expectancy is negatively influenced by CO2emission, ecological footprint, PM2.5, prevalence of undernourishment and unemployment. These variables cause serious health hazards to human health in SAARC countries. The paper gives the recommendations that the authorities should take steps to improve the environmental qualitywhich would lower the health hazards. In this regard, CO2, PM2.5, and undernourishment should be controlled by proper channels. More job opportunities should be created. Government should increase public spending to provide medical facilities. There must be focus on better sanitation services for people. Lastly, the government should raise economicgrowth withmore investments and equal distribution of resources that would improve health outcomes.